Long-term outcome of the adjustable transobturator male system (ATOMS): results of a European multicentre study - Friedl, Alexander; Mühlstädt, Sandra; Zachoval, Roman; Giammò, Alessandro; Kivaranovic, Danijel; Rom, Maximilian; Fornara, Paolo; Brössner, Clemens (BJU international, 2017)
OBJECTIVE: To evaluate the long-term effectiveness and safety of the adjustable transobturator male system (ATOMS® , Agency for Medical Innovations A.M.I., Feldkirch, Austria) in a European-wide multicentre setting. PATIENTS AND METHODS: In all, 287 men with stress urinary incontinence (SUI) were treated with the ATOMS device between June 2009 and March 2016. Continence parameters (daily pad test/pad use), urodynamics (maximum urinary flow rate, voiding volume, residual urine), and pain/quality of life (QoL) ratings (visual analogue scale/Leeds Assessment of Neuropathic Symptoms and Signs, International Consultation on Incontinence Questionnaire-Short Form [ICIQ-SF]/Patient Global Impression of Improvement [PGI-I]) were compared preoperatively and after intermediate (12 months) as well as after individual maximum follow-up. Overall success rate, dry rate (<10 mL/day and 0-1 pad/day), device durability, treatment failure, and device complications were recorded. Nonparametric tests were used for statistical analyses. RESULTS: After a median (interquartile range [IQR]) follow-up of 31 (10-54) months and a median (IQR) of 3 (2-4) adjustments, the overall success rate was 90% (258 men) and the dry rate was 64% (184). Daily pad test and pad use decreased from a median of 400 mL/day and 4 pads/day to a median of 18 mL/day and 1 pad/day (both P < 0.001), concomitantly QoL ratings significantly improved and changed to a high level of satisfaction (PGI-I 4 to 2, ICIQ-SF 17 to 5; both P < 0.001). The UI results at 12 months were comparable to those at final follow-up. Chronic pain and intraoperative complications did not occur. Most of the postoperative complications were Clavien-Dindo grade I-III (no grade IV or V). At present, 231 (80%) of all the ATOMS devices are still functioning; 56 (20%) were removed, the most common reason being local titanium intolerance (41%) and leak/dysfunction (30%). The operating time and continence outcome varied between port generations. In this regard the latest port generation (silicone-covered scrotal port) was superior to its predecessors. Primary implantation (P = 0.002), good physical health (P = 0.001), and no history of radiotherapy (P < 0.001) were prognostic factors for beneficial treatment outcome. CONCLUSION: The ATOMS device is safe and shows high treatment efficacy and patient satisfaction in the largest cohort study to date. The latest generation, with its pre-attached silicone-covered scrotal port, is superior to its predecessors. Significantly better results were achieved with primary implantation and in those without a history of radiotherapy.
Keywords: Suburethral Slings; male stress urinary incontinence; stresová inkontinence moči; suburetrální pásky; Prosthesis Design; výsledek terapie; protézy - design; Time Factors; časové faktory; Urinary Incontinence, Stress; lidé; #Incontinence; long-term outcome; Treatment Outcome; retrospektivní studie; Male; Aged; quality of life; adjustable transobturator male system continence device; senioři; mužské pohlaví; Retrospective Studies; efficacy; Humans